Modal Sosial Penari jathil Obyog Di Kabupaten Ponorogo - Cahyani, Retno Aprin (Paradigma, 2021)
Abstract Jathil Obyog is a unique culture of Ponorogo which is still sustainable today. Jathil Obyog dancers build social capital to maintain their jobs in the midst of the modernization era and in the midst of the negative stigma attached to their dancers. The attachment between Jathil Obyog dancers with groups or communities is interesting to study further. This study aims to analyze the social capital of the dancer JAthil Obyog and identify the background and pattern of relationships formed, using a qualitative method with the social capital approach of Robert Putnam. The results of this study reveal that between dancers build relationship patterns aimed at finding work relationships. Social capital which is divided into three points namely networks, beliefs, values ??and norms is analyzed with findings and creates some conclusions. That the network between dancers is well established for the sake of smooth work and looking for co-workers with fellow dancers. The relationship between dancers and other dancers is also included in social bounding (social glue) and the network that exists between dancers and the community is classified as social bridging (social bridge). While the values ??and norms are in the form of being kind to other dancers and trying to stick to the principles of dancing that are in accordance with the values ??and norms of society or are indecent and not deviant. Keywords: Jathil Obyog, Social Capital, Dancer